Transient receptor potential ankyrin 1 agonists improve intestinal transit in a murine model of postoperative ileus. Issue 12 (10th June 2016) - Tsuchiya, K.; Kubota, K.; Ohbuchi, K.; Kaneko, A.; Ohno, N.; Mase, A.; Matsushima, H.; Yamamoto, M.; Miyano, K.; Uezono, Y.; Kono, T.
Abstract: Background: Stimulation of transient receptor potential ankyrin 1 (TRPA1), which abundantly expressed in enterochromaffin cells (ECC), has been reported to exert apparently contradictory results in in vitro contractility and in vivo gastrointestinal (GI) transit evaluations. The pharmaceutical‐grade Japanese traditional medicine daikenchuto (TU‐100) has been reported to be beneficial for postoperative ileus (POI) and accelerate GI transit in animals and humans. TU‐100 was recently shown to increase intestinal blood flow via stimulation of TRPA1 in the epithelial cells of the small intestine (SI). Methods: The effects of various TRPA1 agonists on motility were examined in a manipulation‐induced murine POI model, in vitro culture of SI segments and an ECC model cell line, RIN‐14B. Key Results: Orally administered TRPA1 agonists, aryl isothiocyanate (AITC) and cinnamaldehyde (CA), TU‐100 ingredients, [6]‐shogaol (6S) and γ ‐sanshool (GS), improved SI transit in a POI model. The effects of AITC, 6S and GS but not CA were abrogated in TRPA1‐deficient mice. SI segments show periodic peristaltic motor activity whose periodicity disappeared in TRPA1‐deficient mice. TU‐100 augmented the motility. AITC, CA and 6S increased 5‐HT release from isolated SI segments and the effects of all these compounds except for CA were lost in TRPA1‐deficient mice. 6S and GS induced a release of 5‐HT from RIN‐14B cells in a dose‐ and TRPA1‐dependent manner. Conclusions & Inferences: Intraluminal TRPA1 stimulation is a potential therapeutic strategy for GI motility disorders. Further investigation is required to determine whether 5‐HT and/or ECC are involved in the effect of TRPA1 on motility. Abstract : Periodic peristaltic motility is lost in TRPA1 KO mice. Intraluminal TRPA1 stimulation may beneficial to POI.